Early detection of intraneural and intravascular injections with real‐time injection pressure monitoring in cadavers. Issue 10 (19th August 2020) - Saporito, Andrea; Quadri, Christian; Steinfeldt, Thorsten; Wiesmann, Thomas; Cantini, Laura Micòl; Capdevila, Xavier
Abstract : Background and Objectives: Injection pressure monitoring can help detecting the needle tip position and avoid intraneural injection. However, it shall be measured at the needle tip in order to be accurate and reproducible with any injection system and non operator‐dependent. With an innovative system monitoring the injection pressure right at the needle tip we show that it is possible to early detect an intraneural and also an intravascular injection. Methods: We performed supraclavicular block‐like procedures under real‐time ultrasound guidance on two fresh cadaver torsos using a sensing needle with an optical fiber pressure sensor within the shaft continuously measuring injection pressure at the needle tip. A total of 45 ultrasound‐guided injections were performed (15 perineural, 15 intraneural and 15 intravenous injections). Results: Mean (SD) injection pressure after only 1 mL injected volume was already significantly higher for the intraneural compared to the perineural injections: 70.46 kPa (11.72) vs 8.34 (4.68) kPa; P < .001. Mean (SD) injection pressure at 1 mL injected volume was significantly lower for the intravascular compared to the perineural injections: 1.51 (0.48) vs 8.34 (4.68) kPa; P < .001. Conclusions: Our results show that injection pressure monitoring at the needle tip has the potential to help identifying an accidental intraneural or intravascular injection at a very early stage.